The implication of parental separation on children in Kuching area / Elvin Mingel - Mingel, Elvin (2002)
This study corresponded to the implications of parental separation on children in the Kuching area. A sample of 100 set of questionnaires that have been distributed in order to seek information and also views as well as opinions from the public concerning our study. The aim of our study is to identify the effects of parental separation on the children, to evaluate whether parental separation is the main cause of social illnesses displayed by youths, and also to seek solutions and give recommendations on how to reduce and overcome the situation. In preparing this report we have faced difficulties in getting the information. Not only that, cooperation from the public is also very poor. However, we were able to manage all the difficulties through cooperation among ourselves as a group